Identifikasi Varietas/Klon Ubikayu Unggul untuk Bahan Baku Bioetanol - Ginting, Erliana; Sundari, Titik; Triwiyono, Bambang; Triatmodjo, Triatmodjo (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2011)
Cassava is a potential source of raw material for bioethanol production. The study was conducted to identify the suitability of the chemical properties of cassava varieties/clones harvested in different seasons to be used as raw material for bioethanol. The trials were conducted at the Experiment Station and the Laboratory of Microbiology, Center for Starch Technology (BBTP), Research and Assessment of Technology (BPPT) Lampung and at the Laboratory of Food Chemistry, Research Institute for Legumes and Tuber, Malang. In 2006, 12 cassava varieties and clones were used, whereas in 2007 eight clones selected from the 12 varieties were used. The crops were harvested at age of 9 months and the tubers were used as raw material for bioethanol production. The experiment was arranged in a randomized complete block design with three replications. The variables observed were chemical composition of fresh tubers and ethanol content of bioethanol produced. Cassava tubers harvested in the rainy season (RS) 2007 contained 1 to 10% more moisture from those harvested in the dry season (DS) 2006, followed by a decrease of starch and total sugar content by 1.4 to 6.6% and 0.5-10%, respectively. Clone CMMM 99008-3 had the highest total sugar content when harvested in the DS 2006 (45.3%), but it was lower (37.0%) in the DS 2006 harvest. In the DS 2006 harvest, four varieties/clones had conversion values 4.2 to 4.5 kg of fresh tuber to one liter of 96% bioethanol, i.e., CMM 99008-3, MLG 0311, OMM 9908-4, and UJ-5. In the WS 2007 harvest, four varieties/clones showed conversion values from 4.5 to 5 kg to one liter of 96% bioethanol, i.e., CMM 99008-3, UJ-3, UJ-5, and OMM 9908-4. Five cassava clones harvested in the RS 2007, namely CMM 99008-3, UJ-3, UJ-5, MLG 0311, and OMM 9908-4 produced tubers yield ranging from 29.3 to 38.2 t/ha. Clone UJ-5 produced the highest bioethanol (7,866 l/ha).